'So, he is practically a Korean?': Power relations and re-articulation of the Korean Self in the TV show Non-Summit. Issue 2 (1st August 2020) - Eydam, Tanja
Korean national identity is defined by nationalist sentiment and a mono-ethnic self-image. Having turned into a migrant-receiving country, Korea is slowly transforming into a multicultural society. The contemporary popularity of television shows with migrant representation reflects this change. The question arises how migrants get depicted in these popular broadcasting shows and what this portrayal of non-Koreans reveals about re-articulations of the Korean Self. As a response to these questions, a critical discourse analysis of Episodes 1 and 103 of the show Non-Summit (Bijeongsang hoedam 2014–17) is conducted. Corresponding to Koller's (2011) combined discourse-historical and socio-cognitive approach, macro-, meso- and micro-level are analysed separately. Overall, Non-Summit reproduces Korean discourse on multiculturalism as 'happy talk', as the avoidance of in-depth consideration of inequality, the reproduction of 'western' norms and the normativity of Koreanness. This results from predominantly selecting Caucasians and constructing them as 'para-Koreans' who can then be readily consumed. These practices enable the Korean Self to position itself as analogous to western, modern norms. This positioning mirrors the influence of 'nouveau-riche nationalism' and the Korean 'will to greatness'. The show further consolidates existing societal norms in Korea (Kang 2017: 14) on four different levels of power relations between Korean producers/writers and migrant population in Korea, non-Korean cast and migrant population in Korea, Korean producers/writers/hosts and non-Korean cast, and Korean viewers and non-Korean cast, and hierarchizes modern and traditional values. Thereby, Non-Summit reproduces the South Korean struggle to reconstruct a homogenous national identity in the face of a rising ethnic diversity within the country.